Three-position gearshifts remote control for agricultural tractors - Thewin Sakunbunyong; Tossapol Jangnoi; Tanawat Chalardsakul; Viroch Sukontanakarn (Universitas Ahmad Dahlan, 2025)
This research presents the development and evaluation of a three-position gearshifts remote control system for agricultural tractors, designed to improve operational efficiency and reduce operator fatigue. The system utilizes a programmable logic controller to remotely control a linear actuator, enabling seamless gear shifting between three predetermined positions. The primary objective is to provide operators with a convenient, ergonomic alternative to traditional manual gear shifting, particularly in challenging or confined working environments. The system was tested under two conditions: first, with a programmable logic controller controlling the linear actuator via a remote transmitter; second, with the system installed on an actual tractor and tested in a road scenario. Results from both tests demonstrate the system’s effectiveness in enhancing ease of operation, reducing physical strain, and maintaining gearshifts precision. The findings suggest that the remote control system offers significant potential for improving tractor operation, particularly for tasks requiring frequent gear changes or when working in difficult terrain. This research contributes to the ongoing development of automation in agricultural machinery, offering insights into remote control applications and the integration of electromechanical systems in agricultural vehicles.